Kenyah forest use in East Kalimantan: responses to El Nino, transmigration and HTI - Colfer, C.J.P.; Salim, A. (1998)
This paper recounts of a household survey done in Long Segar, East Kalimantan, in June 1997, covering the period from 1991-1997. This survey is a follow-up survey of land use, conducted first in 1980 (1962-1980) and again in 1991 (1981-1991). The initial purpose of the 1997 survey was to assess changes in land use since the development of industrial timber plantations near Long Segar. During the study period, there were two El Nino events. The results show fewer significant changes from previous conditions than expected. Cutting of old growth forest rice fields has dismished precipitously from previous level. Old secondary forest is now the dominant forest type used for swiddens. Yields have fallen from an average of 1.2 tons/ha to one ton/ha. Individual field size has increased while households had four consecutive studies. Recourse to wage labour has increased considerably, in response to agricultural failures. Standard of living appears not to have fallen disastrously. Ownership of chainshaws and outboard motors has increased. Women's traditionally dominant role in rice production seems to be holding its own (contrary to previous predictions), with slightly more agriculturally active a men per household, but a greater impact of women's input on rice production. It is concluded that the Long Segar community is coping by creative use of opportunities when its rice crops fails. But further studies to assess the possibility that the dramatic reduction in natural forest cover precipitated by other parties in the area (transmigration, logging, industrial timber plantation) may be having an impact on Long Segar's micro-climate, with potentially long term and disastrous effects. This year is predicted to be the 'Mother of all El Nino's".